A Hydrogeological Investigation of the Chocaya Alluvial Fan in Cochabamba, Bolivia - Öhman,Erik; Slaatto,Kristian (2024)
The Central Valley of Cochabamba is located in the Andes mountain range, Bolivia. This region experiences several water related challenges such as a scarcity of surface water, an increasing water demand, a growing urbanization in groundwater recharge areas, and a declining water table due to intensive groundwater extraction. The valley has been influenced by both alluvial and fluvial depositions that have shaped its geology, resulting in a complex lithological profile throughout the valley. The center of the valley contains more fine-grained sediment layers, while the northern and eastern parts consist of more coarse-grained depositions that is more beneficial from a groundwater extraction standpoint. Consequently, several groundwater wells have been constructed in the northern and eastern parts, supplying large populations within the valley with fresh water. The aim of this investigation is to map a part of the geometry of an alluvial fan, located in the northern part of the valley. This area is important for groundwater extraction and is delimited by the two rivers Chocaya and Chijllawiri. The mapping is performed using the geophysical methods Electrical Resistivity Tomography (ERT) and Transient Electromagnetics (TEM) and the results from the geophysical surveys are then compared with lithological profiles from wells in the area. Overall, the geophysical measurements are mostly conducted in open terrain in close proximity to farmland. However, parts of the area are urbanized, leading to difficulties in achieving a comprehensive geophysical mapping. Besides investigating the geometry of the aquifer, a hydrochemical and isotopic analysis of groundwater, surface water and precipitation is conducted to understand recharge processes and interconnections within the aquifer system in the area. The geophysical results indicate that a 10-20 m thick surface layer with fine-grained sediments covers the study area. This is followed by a layer of considerable thickness of 30-100 m that appears to contain more coarse-grained sediments. Moreover, a potential aquifer could be distinguished at a depth of 110-140 m where the resistivity drastically decreases in large parts of the survey area. This potential aquifer level is also supported by farmers that use groundwater wells throughout the area. The hydrochemical and isotopic analysis shows that the Chocaya river likely is an important recharge source of groundwater in the aquifer system. Moreover, the analysis indicates a high interconnection within the aquifer with the groundwater approximately flowing in a southeastern direction throughout the aquifer system.
Keywords: Hydrogeology; Geophysics; Isotopic Analysis; Hydrochemistry; Aquifer; Alluvial Fan.